Predicting post-deployment family adaptation in U.S. Navy families - Scott, Micah; Condon, Esther; Montgomery, Arlene; Baker, Spencer (International Journal of Advanced Nursing Studies, 2014)
Background: Although military families worldwide face changes that include adapting to peace and wartime deployments, few studies have explored how military families adapt to the post-deployment return of a service member. Objectives: To identify variables that predicted post-deployment adaptation of U.S. Navy families. Methods: A mixed method study guided by the Roy Adaptation Model included a convenience sample of 142 spouses of service members recently returned from deployment. The degree to which length of deployment, prior deployments, and years married, number of children, participation in religious and family support groups, communication, race, and interdependence predicted post-deployment family adaptation was tested. Multiple regression analysis and content analysis were used to analyze quantitative and qualitative data to better understand post- deployment adaptation of military families. Results: Post-deployment family adaptation was significantly predicted by having been previously deployed and by scores measuring family interdependence. Content analysis of qualitative responses from 10 spouses indicated that 90% experienced integrated adaptive responses. Conclusions: Family interdependence and prior deployments predicted levels of post-deployment family adaptation. Families who “give time” to adjust, communicate, and resume family routines experienced levels of adaptive response. Keywords: Deployment, Family, Family Nursing, Military Families, Spouse.